Karate and Dance Training to Improve Balance and Stabilize Mood in Patients with Parkinson’s Disease: A Feasibility Study - Dahmen-Zimmer, Katharina; Jansen, Petra (Frontiers in Medicine, 2017)
The present pilot study investigated the effect of karate (according to the rules of the German-Karate-Federation) and dance training compared to an inactive control group in patients with Parkinson’s disease (PD). 65 patients were recruited of which 25 took part in karate training, 12 in dance training and 18 in the control group according to their personal preference. Before and after the whole training phase cognitive performance, emotional wellbeing and balance were measured. The results showed that both, karate and dance training groups, improved balance. Furthermore, the mood dropped only in the waiting control group receiving no training at all, whereas it remained stable in patients who attended the karate and dance group. The training adherence was higher in the karate than the dance group indicating a high acceptability in PD patients for karate. In sum, karate can have the same positive effects as dance for PD patients. Further studies with larger samples and more rigorous methodologies are required to investigate the reported effects in more detail.